Tuberculosis research questions identified through the WHO policy guideline development process. Issue 3 (19th March 2019) - Gebreselassie, Nebiat; Falzon, Dennis; Zignol, Matteo; Kasaeva, Tereza
High-quality research evidence is critical for improving global health and health equity, and for achieving the World Health Organization (WHO)'s objective of the attainment of the highest possible level of health by all peoples [1]. This need is most apparent when responding to complex epidemics such as tuberculosis (TB). TB is the leading killer among diseases caused by an infectious agent worldwide, the leading killer of people with HIV infection and a leading cause of death from airborne anti-microbial resistant infections, taking heavy tolls on human lives, communities and health systems at large [2, 3]. WHO guideline development groups identify research questions using systematic reviews, economic analyses and stakeholder consultations during policy guidance development to identify urgent research gaps in the policy/implementation interface http://ow.ly/lUUw30nQZRO